Cantaxantina em dietas com milho ou sorgo sobre os parâmetros reprodutivos de galos - Forgiarini, Juliana (2015)
This study was carried out at the Poultry Science Laboratory (LAVIC) of Federal University of Santa Maria (UFSM). The objective was to evaluate the antioxidant effect of canthaxanthin on diets with or without addition of carotenoids to breeding males. It was used a total of 48 White Plymouth Rock breed hens from the 48th to the 59th week of age in a completely randomized design in a factorial arrangement, with two ingredients (corn or sorghum), and two levels of canthaxanthin (0 mg/kg or 6 mg/kg) totaling four experimental diets with 12 repetitions, being each hen considered a repetition. The experimental phase was divided into 3 periods of 28 days, to evaluate the performance of the hens. The evaluated parameters were: body weight, food consumption, semen volume, sperm motility, sperm vigor, sperm concentration and fertility. All parameters, except the sperm concentration, were not affected by the diets. The sperm concentration was significantly affected by the ingredient corn and by the canthaxanthin supplementation in the third period (56th to 59th week of age). The use of sorghum is suggested in the diets of roosters with no need of canthaxanthin supplementation. Researches in breeding males and the use of new antioxidants may help in better reproductive rates in poultry.